Greenhouse gas mitigation in pasture-based dairy production systems in New Zealand: A review of mitigation options and their interactions - Kalehe Kankanamge E; Ramilan T; Tozer PR; de Klein C; Romera A; Pieralli S (Elsevier B.V., 2025)
Reducing greenhouse gas (GHG) emissions from dairy farming is crucial for mitigating climate change and enhancing the environmental credentials of New Zealand's dairy exports. This paper aims to explore potential GHG mitigation measures and their interactive effects when combined within New Zealand context, emphasising the practicality of these combinations, particularly focusing on recent studies of pasture-based dairy systems. The review assesses various mitigation options across animal, manure management, feed-based, soil-related, and system-related interventions and identifies immediately applicable mitigation options based on specific criteria. It also discusses the implementation costs, implications on emissions, and the combined effects of these options when applied as bundles in pasture-based systems using a combination matrix. It is indicated that mitigation options on New Zealand's dairy farms can yield diverse outcomes and costs based on farming characteristics. By analysing different combinations of short-listed, it was found that although most mitigation options are compatible, some may have a lower overall reduction potential because of interaction effects. Integrating lower N fertiliser use, low-emission feed, and reduced stocking rates with high-performing animals provides a practical approach for GHG reductions and potential cost savings. However, implementing compatible mitigation bundles requires better quantification of their interactions, economic viability, and compatibility with existing farming systems which need further research.
Keywords: Greenhouse gases; Climate change; Environment; Technology; Pasture-based